Impact of organic weed and nutrient management practices on soil physico-chemical properties and nutrient balance in Maize (Zea mays L.) of western Rajasthan - Jain, Lokesh Kumar; Verma, Mahendra Prakash; Parewa, Hanuman Prasad; Choudhary, Anirudh (Journal of Cereal Research, 2023)
An experiment was conducted during kharif 2019 to 2020 at Instructional Farm, College of Agriculture, Sumerpur (Rajasthan) to study the impact of integrated methods of weed management and organic nutrient sources on soil physical properties and balance sheet after maize harvest (Zea mays L.). The experiment comprises 06 weed management and 05 nutrient management practices in split-plot design with three replications. The treatments stale seedbed + hoeing once at 20 DAS + application of 5 t ha-1 of straw mulch at 30 DAS and weed free check maintained up to 60 DAS of maize however found significantly effective in increasing the crop productivity but improved the above properties non significantly over rest of treatments. The soil physico-chemical properties viz., pH & EC and available nutrients viz., N, P2O5, K2O, Zn and Fe in soil did not influence significantly by various weed management treatments after harvest of maize except organic carbon content. The nutrient balance was negative but minimum was in weed free check and stale seedbed + hoeing at 20 DAS + straw mulch at 30 DAS. Among the organic nutrient management treatments, 75% RDN through vermicompost in two split + seed treatment with beejamurt + two sprays of jeevamurt did not affect the soil physio-chemical properties viz., pH & EC and available nutrients (Fe and Zn) in soil after harvest of maize was remained unaffected while the available NPK and organic carbon of soil was influenced significantly during the study period. The treatment 100% RDN through FYM gave the mean maximum values of these parameters while the lowest was recorded in treatment 75% RDN through vermicompost + seed treatment with beejamurt + two sprays of jeevamurt (at 500 l ha-1 at sowing and 30 DAS). The balance sheet indicated that minimum net loss of nitrogen was in 100% RDN through vermicompost while phosphorus and potassium was recorded in 100% RDN through FYM at the end of the experiment. The mean available nitrogen, phosphorus and organic carbon in the soil were also significantly increased in this treatment. The balance sheet indicated that minimum net loss of nitrogen, phosphorus and potassium was recorded in treatment 75% RDN through vermicompost + seed treatment with beejamurt + two sprays of jeevamurt.